INTERLINGUAL PROBLEMS IN TEACHING FOREIGN LANGUAGES: THE CONCEPT OF INTERFERENCE AND MODERN SOLUTIONS - Farkhod Boltaboyev (Western European Studies, 2024)
The article "Interlingual Problems in Teaching Foreign Languages: The Concept of Interference" provides a comprehensive exploration of the challenges encountered in language acquisition, with a specific focus on the concept of interference. The author adopts a structured approach, following the IMRAD (Introduction, Methods, Results, and Discussion) format to present a systematic analysis of the topic.
Keywords: interlingual; interference; fossilization; overgeneralization